Safety and efficacy of cognitive training plus epigallocatechin-3-gallate in young adults with Down's syndrome (TESDAD): a double-blind, randomised, placebo-controlled, phase 2 trial - de la Torre, Rafael; de Sola, Susana; Hernandez, Gimena; Farré, Magí; Pujol, Jesus; Rodriguez, Joan; Espadaler, Josep María; Langohr, Klaus; Cuenca-Royo, Aida; Principe, Alessandro; Xicota, Laura; Janel, Nathalie; et al. (Lancet neurology, 2016)
Early cognitive intervention is the only routine therapeutic approach used for amelioration of intellectual deficits in individuals with Down's syndrome, but its effects are limited. We hypothesised that administration of a green tea extract containing epigallocatechin-3-gallate (EGCG) would improve the effects of non-pharmacological cognitive rehabilitation in young adults with Down's syndrome. We enrolled adults (aged 16–34 years) with Down's syndrome from outpatient settings in Catalonia, Spain, with any of the Down's syndrome genetic variations (trisomy 21, partial trisomy, mosaic, or translocation) in a double-blind, placebo-controlled, phase 2, single centre trial (TESDAD). Participants were randomly assigned at the IMIM-Hospital del Mar Medical Research Institute to receive EGCG (9 mg/kg per day) or placebo and cognitive training for 12 months. We followed up participants for 6 months after treatment discontinuation. We randomly assigned participants using random-number tables and balanced allocation by sex and intellectual quotient. Participants, families, and researchers assessing the participants were masked to treatment allocation. The primary endpoint was cognitive improvement assessed by neuropsychologists with a battery of cognitive tests for episodic memory, executive function, and functional measurements. Analysis was on an intention-to-treat basis. This trial is registered with ClinicalTrials.gov, number NCT01699711. The study was done between June 5, 2012, and June 6, 2014. 84 of 87 participants with Down's syndrome were included in the intention-to-treat analysis at 12 months (43 in the EGCG and cognitive training group and 41 in the placebo and cognitive training group). Differences between the groups were not significant on 13 of 15 tests in the TESDAD battery and eight of nine adaptive skills in the Adaptive Behavior Assessment System II (ABAS-II). At 12 months, participants treated with EGCG and cognitive training had significantly higher scores in visual recognition memory (Pattern Recognition Memory test immediate recall, adjusted mean difference: 6·23 percentage points [95% CI 0·31 to 12·14], p=0·039; d 0·4 [0·05 to 0·84]), inhibitory control (Cats and Dogs total score, adjusted mean difference: 0·48 [0·02 to 0·93], p=0·041; d 0·28 [0·19 to 0·74]; Cats and Dogs total response time, adjusted mean difference: −4·58 s [–8·54 to −0·62], p=0·024; d −0·27 [–0·72 to −0·20]), and adaptive behaviour (ABAS-II functional academics score, adjusted mean difference: 5·49 [2·13 to 8·86], p=0·002; d 0·39 [–0·06 to 0·84]). No differences were noted in adverse effects between the two treatment groups. EGCG and cognitive training for 12 months was significantly more effective than placebo and cognitive training at improving visual recognition memory, inhibitory control, and adaptive behaviour. Phase 3 trials with a larger population of individuals with Down's syndrome will be needed to assess and confirm the long-term efficacy of EGCG and cognitive training. Jérôme Lejeune Foundation, Instituto de Salud Carlos III FEDER, MINECO, Generalitat de Catalunya.